Revestimento nanoestruturado de cera de carnaúba na manutenção da qualidade pós-colheita de tomates - Miranda, Marcela (Universidade Federal de São Carlos, 2015)
Tomato is one of the most popular and consumed vegetable. However it is highly perishable because of its high water content. Post-harvest technologies of fruits and vegetables try to increase the shelf life of fruits, to keep quality and to reduce quantitative and qualitative losses between harvest and consumption. One of these technologies is based on the use of coatings on fruits and vegetables, because they are effective in reducing water loss and maintaining the quality of fresh products. This study aimed to synthesize and compare conventional emulsion and nanoemulsion of carnauba wax, as well as to evaluate the influence of different concentrations of these coatings on tomatoes (Solanum lycopersicum) during storage. Therefore, emulsions with different particle sizes were synthesized and characterized by particle size measurements (hydrodynamic diameter); zeta potential (colloidal stability); polydispersity index; scanning electron microscopy images; contact angle and stability in different environments. In sequence, the emulsions were applied on 'Débora' and 'Pizzadoro' cultivar tomatoes to evaluate the effect of these coatings on the physical and chemical quality and the internal atmosphere of the fruits. For that purpose, the following experiments were performed: (I) 'Débora' cv Tomatoes were coated with conventional emulsion and nanoemulsion at concentrations 9% and 18% and stored at 23 °C ± 1 (80% RH) for 16 days. Assessments of physical chemical and gases analyses (ethylene, CO2 and O2) were carried out. (II) 'Pizzadoro' cv Tomatoes were coated with conventional emulsion and nanoemulsion at concentrations of 9% and 18% and stored at 23 °C ± 1 (80% RH) for 13 days and the same quality analyses were carried out. (III) Sensory analysis in 'Deborah' cv tomatoes coated with conventional emulsion and carnauba wax nanoemulsion at concentrations 9% and 18% and stored at 23 ° C ± 1 (80% RH) for 10 days, were evaluated for the visual appearance, purchase intent and ordering by preference. Nanoemulsions showed smaller particle size and polydispersivity compared to conventional emulsion. In post-harvest tests, fruits coated with emulsions showed lower weight loss rate than control fruits. 'Pizzadoro' cv tomatoes coated with both emulsions appeared to be clearer and less red at the end of storage than the control sample. Nanoemulsion carnauba wax did not change the barrier property of the coating responsible for controlling water permeation, and presented performance similar to conventional emulsion. The nanoemulsion showed more acceptance, purchase intent and preference by tasters in the sensory test, probably due to the high brightness attained by this coating.
Keywords: Nanoemulsão; Emulsão convencional; Coberturas comestíveis; Conservação; Solanum lycopersicum; Nanoemulsion; Conventional emulsion; Edible coatings; Conservation; OUTROS